Cultural studies : a critical introduction - During, Simon, 1950- (Routledge, 2005)
This book is not quite the usual introduction to cultural studies an academic field thatwe can define, without messing about, as the engaged analysis of contemporarycultures. Cultural studies is engaged in three different senses. First, in the sense that it isnot neutral in relation to the exclusions, injustices and prejudices that it observes. Ittends to position itself on the side of those to whom social structures offer least, so thathere engaged means political, critical. Second, it is engaged in that it aims to enhanceand celebrate cultural experiences: to communicate enjoyment of a wide.